2022
DOI: 10.1016/j.jmsacl.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Infrared multiple photon dissociation (IRMPD) spectroscopy and its potential for the clinical laboratory

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 115 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…This inquiry originates from the current, increasing interest in the application of IR spectroscopy as a versatile analytical tool to clarify the structural features of small (bio)molecules involved in relevant metabolic functions. 31 , 37 41 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inquiry originates from the current, increasing interest in the application of IR spectroscopy as a versatile analytical tool to clarify the structural features of small (bio)molecules involved in relevant metabolic functions. 31 , 37 41 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, quantum chemical calculations have been performed to sample low-energy candidate isomers and to obtain optimized geometrical and electronic structures and linear IR absorption spectra. This inquiry originates from the current, increasing interest in the application of IR spectroscopy as a versatile analytical tool to clarify the structural features of small (bio)­molecules involved in relevant metabolic functions. , …”
Section: Introductionmentioning
confidence: 99%
“…The IR-FEL is generated by the strong interaction of SR with the successive electron beam and is transmitted from a coupling hole in the center of a resonant mirror to a laboratory. A remarkable feature of the IR-FEL is that it gives intense vibrational excitation energy to the corresponding functional group's mode-selectively, which can induce multi-photon absorption and dissociation reactions for various molecules in gas, liquid, and solid phases [23][24][25][26]. We have previously found that cellulose fibers can be dissociated, and glucose and low-molecular weight oligosaccharides can be recovered using an IR-FEL tuned to 9.1 µm (νC-O), 7.2 µm (δH-C-O), and 3.5 µm (νC-H) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational resonances are highly sensitive to details of the molecular structure, such that closely related isomeric molecular ions can often be differentiated on the basis of their IR spectra. Indeed, a range of studies have shown that IRIS can distinguish isomeric small molecules [16][17][18][19][20][21][22][23][24][25][26][27][28] , including several phase-I drug metabolites [29][30][31] . A significant advantage in comparison to techniques based on MS/MS fragmentation patterns is that gas-phase IR spectra can be reliably and efficiently predicted using quantum-chemical calculations based on density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%